Os efeitos dos slogans nos discursos da educação e o silêncio que significa: leitura dos editoriais dos jornais Folha de S. Paulo e O Estado de S. Paulo - Silva, Adriana (2011)
Folha de S.Paulo and O Estado de S.Paulo newspapers were sources of a study about the presence of slogans in educational speeches. This research asserts that communication by slogans damages the understanding of the message that is intended to be conveyed because once it´s effective, slogans cease the debate and damage the reflection about the theme that is being discussed. It can be concluded that the slogan “Education to everyone gave place to “Education with quality”, but it also alerts that the sense of quality presented itself as related to the idea that education is meant to make people able to find jobs. As the newspapers alert, once they are businesses, they are ideologically related to the market and when they choose to announce a specific piece of news, they automatically obscure another that, by being kept in silence, also symbolizes, in this research, the silence of education that combats reifying.